The comparison among Prime Bank and other enlisted banks’ management practice of upholding provision against financial aspects - Ripa, Afroza Sultana (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.